2002
DOI: 10.1002/jsfa.1124
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antiradical and reducing properties of selected Greek white wines: correlation with polyphenolic composition

Abstract: The total hydroxycinnamate (THC) and total¯avanol (TF) contents were determined in 26 selected Greek white wines of`Appellation of Origin of High Quality' using well-established spectrophotometric methodology. Furthermore, two parameters related to the antioxidant capacity of wines, the antiradical activity (A AR ) and the reducing power (P R ), were also determined using the stable DPPH . radical and a ferric reducing power assay respectively. THC content varied from 64.4 to 197.1 mg l À1 chlorogenic acid equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
25
1
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 48 publications
(46 reference statements)
11
25
1
5
Order By: Relevance
“…With the DPPH method, antioxidant activity and total phenolics of black tea extracts correlated significantly at 2, 8 and 18 h of extraction (R 2 =0.89, 0.85 and 0.84, respectively). Contrary to the results of Psarra et al [28] on wines, this study showed that correlation of RP with total polyphenols is stronger than that of radical scavenging activity, which can be attributed to different reactivity of polyphenols in black tea in different antioxidant assays.…”
Section: Antioxidant Activitycontrasting
confidence: 99%
See 1 more Smart Citation
“…With the DPPH method, antioxidant activity and total phenolics of black tea extracts correlated significantly at 2, 8 and 18 h of extraction (R 2 =0.89, 0.85 and 0.84, respectively). Contrary to the results of Psarra et al [28] on wines, this study showed that correlation of RP with total polyphenols is stronger than that of radical scavenging activity, which can be attributed to different reactivity of polyphenols in black tea in different antioxidant assays.…”
Section: Antioxidant Activitycontrasting
confidence: 99%
“…Satoh et al [27] also observed that there was a strong correlation between the RP and total phenolic content of different tea extracts including black tea. However, Psarra, et al [28] found a poor correlation (R 2 =0.60) between RP and total polyphenol of wines and also a high correlation (R 2 =0.81) for radical scavenging activity. The differences may be due to the different polyphenol composition of materials investigated.…”
Section: Antioxidant Activitymentioning
confidence: 97%
“…A previously established method described by Psarra et al (2002) was employed with modifications. An aliquot of 0.05 mL of extract was mixed with 0.05 mL FeCl 3 (3 mM in 5 mM HCl).…”
Section: Reducing Powermentioning
confidence: 99%
“…Hence the beneficial properties of wines have been mainly interpreted on the basis of the antioxidant properties on the flavonoid fraction, which are related to both free radical scavenging and transition metal chelating . However, because of the different types of grapes used and the different production processes implemented, there are fundamental and crucial differences in white and red wine composition in terms of both the nature and quantity of polyphenols (Psarra, Makris, Kallithraka, & Kefalas, 2002).…”
Section: Introductionmentioning
confidence: 99%